Presentation of Coastal Environmental Management Plan by using SWOT/AHP methods - R Sharifipour; B Mahmodi (Journal of Applied Sciences and Environmental Management)
The provision of environment management plan and formulating the environmental strategies of coastal regions are the most essential measures required for the integrated management of coastal regions. For this purpose, this research has been conducted using two goal-oriented and problem-oriented approaches in order to determine the planning perspective and problems approach in order to determine bottlenecks respectively. At first, the vision, mission, and objective of developing the environmental management of the eastern coasts of Mazandaran by SWOT (Strengths-Weaknesses-Opportunities-Threats) method have been determined. Thereafter, with using of analytic hierarchical process (AHP) method and EC (Expert chose) software have been applied to prioritize the strategies. At last, the environmental plan and projects of this region was provided based on the objectives. According to this research, the macro-strategies of SO, WO, ST, and WT have been identified in the said order as the priorities of the environmental planning of the region. The SO strategies including the protection of aquatics, integrated management of rivers and surface waters, and the development of coastal tourism as well as the most prioritized one, which is the optimal management of environment and sensitive ecosystems of coastal regions have been studied. In general, in this research 18 environmental strategies classified into four strategic classes have been defined. According to the six objectives, 10 plan, and 16 projects have been defined for the environmental management plan of the eastern coasts of Mazandaran Province.